2019
DOI: 10.1139/cjas-2018-0085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the sex and type of tissue on the basic chemical composition and the content of minerals in the sirloin and offal of fattener pigs

Abstract: The aim of the study was to determine the basic chemical composition and mineral content in the sirloin and offal of fattener pigs, taking their sex into consideration. In addition, comparative analysis of the content of chemical and mineral components in the sirloin and offal was performed. The experimental material included 24 crossbred (Polish Landrace × Polish Large White) fatteners, from which samples of sirloin (musculus longissimus lumborum), liver, heart, and kidneys were collected for the analysis. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 11 publications
3
24
0
1
Order By: Relevance
“…As reported by Dannenberger et al (2013), wild boar meat contains around quadruple higher Fe levels than the meat of domestic pigs. Similar results of the Fe concentration in domestic pigs were obtained by Cebulska (2015) in the Pulawska and Złotnicka Pstra breeds and by Gali an et al (2008) in Chato Murciano and Babicz et al (2018) in hybrid (PL Â PLW) fatteners. Importantly, Fe contained in meat is haem iron, which is absorbed at a several-fold higher level than the non-haem iron present in other raw materials and food products (Soetan et al 2010;Nishito and Kambe 2018).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As reported by Dannenberger et al (2013), wild boar meat contains around quadruple higher Fe levels than the meat of domestic pigs. Similar results of the Fe concentration in domestic pigs were obtained by Cebulska (2015) in the Pulawska and Złotnicka Pstra breeds and by Gali an et al (2008) in Chato Murciano and Babicz et al (2018) in hybrid (PL Â PLW) fatteners. Importantly, Fe contained in meat is haem iron, which is absorbed at a several-fold higher level than the non-haem iron present in other raw materials and food products (Soetan et al 2010;Nishito and Kambe 2018).…”
Section: Discussionsupporting
confidence: 82%
“…In investigations on the impact of the rearing system (conventional and organic) on the mineral content, Zhao et al (2016) found mean Mn values of 0.473 and 0.695 mgÁkg À1 (respectively). Lower concentration of this element was noted in the muscle of hybrid (PL Â PLW) by Babicz et al (2018). The recommended daily intake of manganese is 3 mg/d in adults (EFSA 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Red meat is an important source of minerals in the human diet, as it provides highly bioavailable elements required for normal development and health [19]. Minerals contained in meat, in comparison with those present in plants, are more easily absorbed [20].…”
Section: Introductionmentioning
confidence: 99%